Wood Energy in the ECE Region: Data, Trends and Outlook in Europe, the Commonwealth of Independent States and North America - UN Economic Commission for Europe (UNECE); Aguilar Francisco X; Food and Agriculture Organization (New York: United Nations Publication, 2018)
The report discusses types of wood energy fuels such as firewood, sources and users, policy instruments that support and hinder use, and ways to sustainably source wood. The report also, inter alia: describes how social, economic and political trends and developments may impact on wood energy use and sustainable production; includes statistics on wood energy markets across the UNECE region; helps bridge information about the forest and energy sectors; provides information on the role of wood energy in a range of sectors to support green economy strategies; and outlines commercial wood energy uses.
Keywords: Wood energy; Forest; Wood - Combustion; Forest productivity; Green economy; Fuelwood